2010
DOI: 10.1007/s00403-010-1113-9
|View full text |Cite
|
Sign up to set email alerts
|

Major translocation of calcium upon epidermal barrier insult: imaging and quantification via FLIM/Fourier vector analysis

Abstract: Calcium controls an array of key events in keratinocytes and epidermis: localized changes in Ca2+ concentrations and their regulation are therefore especially important to assess when observing epidermal barrier homeostasis and repair, neonatal barrier establishment, in differentiation, signaling, cell adhesion, and in various pathological states. Yet, tissue- and cellular Ca2+ concentrations in physiologic and diseased states are only partially known, and difficult to measure. Prior observations on the Ca2+ d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 86 publications
1
19
0
Order By: Relevance
“…Figure 1a and b represent the averaged position of the calcium concentration peaks in each epidermal layer. We observed a dramatic shift of the calcium concentration distribution toward higher calcium levels immediately after barrier perturbation in all epidermal layers (Figure 1a and b, respectively, and Supplementary Figure S1) in agreement with data previously reported in mice (Behne et al, 2011). To monitor calcium fluxes during barrier recovery, we imaged tape-stripped and acetone-treated samples 4 and 24 hours after perturbation.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Figure 1a and b represent the averaged position of the calcium concentration peaks in each epidermal layer. We observed a dramatic shift of the calcium concentration distribution toward higher calcium levels immediately after barrier perturbation in all epidermal layers (Figure 1a and b, respectively, and Supplementary Figure S1) in agreement with data previously reported in mice (Behne et al, 2011). To monitor calcium fluxes during barrier recovery, we imaged tape-stripped and acetone-treated samples 4 and 24 hours after perturbation.…”
Section: Resultssupporting
confidence: 92%
“…While initial studies using fixed and sectioned tissue (Mauro et al, 1998; Menon et al, 1992) showed that after acute barrier perturbation, Ca 2+ drops in the viable layers and then recovers as the barrier recovers, a more recent study (Behne et al, 2011) reported a moderate increase in intracellular and extracellular calcium concentration as soon as 30 minutes after barrier perturbation by acetone lipid extraction in hairless mice. We find that the conflicting results on the Ca 2+ gradient response to barrier perturbation reported by different groups can be attributed to different experimental preparations (see Supplementary Figure S3 online).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, dynamic intravital fluorescence lifetime imaging (FLIM) is required [52][53]. Here we present a novel parallelized TCSPC (p-TCSPC) device featuring a 80 MHz average count rate, enabling us to demonstrate 4D-FLIM in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In normal skin, there is a characteristic intraepidermal calcium gradient, with peak concentrations in the stratum granulosum and lowest levels in the stratum basale. [7][8][9] Ca 2 + plays an important role in keratinocyte differentiation 10 and in regulation of lamellar body secretion during barrier recovery. 11 Normal skin also has a pH gradient where the SC has pH 4.5-5.5 and the viable epidermis displays neutral pH.…”
mentioning
confidence: 99%